Gambaran Womac Index dan Range of Motion Aktif Pada Pasien Osteoarthritis Genu di RSUD Waled Kabupaten Cirebon - Tina Astuti; Moh. Irwan Dharmansyah; Taufan Herwindo Dewangga; Siti Maria Ulfah (Universitas Malahayati Lampung, 2026)
ABSTRACT Osteoarthritis is a degenerative condition of the joints that causes damage to the joint cartilage, thickening of the bone underneath the cartilage, bone formation around the joint edges, and mild inflammation of the synovial lining. Risk factors for this disease include age, female gender, obesity, physical activity level, genetic factors, race, joint trauma, physical inactivity, obesity, and metabolic diseases such as diabetes can worsen the condition of OA. To measure activities of daily living and body function the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) is an appropriate measurement tool to assess activities of daily living and body function and Range Of Motion to assess joint movement. Knowing the description of the WOMAC index and active range of motion in patients with genu osteoarthritis at Waled Hospital, Cirebon Regency. This study uses a quantitative descriptive method, which aims to get an overview or description of a situation objectively. Data were collected using total sampling technique and 32 samples were obtained. Patients diagnosed with genu Osteoarthritis were 32 (100.0%), the majority were aged 45-59 years 18 (56.3%), mostly female 27 (84.4%), with the most womac index score obtained as heavy as 16 (50.0%) and the majority of active range of motion was limited to the right leg with flexion 29 (90.6%) and extension 19 (59.4%). Osteoarthritis genu patients totaling 32 patients, the majority aged 45-59 years, mostly female with the results of the womac index obtained heavy and the results of active range of motion are mostly limited. Keywords: Osteoarthritis, Womac Index, Active Range of Motion. ABSTRAK Osteoartritis adalah kondisi degeneratif pada sendi yang menyebabkan kerusakan pada kartilago sendi, penebalan tulang di bawah kartilago, pembentukan tulang di sekitar tepi sendi, serta peradangan ringan pada lapisan sinovial. Faktor risiko penyakit ini meliputi usia, jenis kelamin perempuan, obesitas, tingkat aktivitas fisik, faktor genetik, ras, trauma sendi, kurangnya aktivitas fisik, obesitas, serta penyakit metabolik seperti diabetes dapat memperburuk kondisi OA. Untuk mengukur aktivitas kehidupan sehari-hari dan fungsi tubuh Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) adalah alat ukur yang tepat untuk menilai aktivitas kehidupan sehari-hari dan fungsi tubuh dan Range Of Motion untuk menilai gerakan sendi. Mengetahui gambaran womac index dan range of motion aktif pada pasien osteoarthritis genu di RSUD Waled Kabupaten Cirebon. Penelitian ini menggunakan metode deskriptif kuantitatif, yang bertujuan untuk mendapatkan gambaran atau deskripsi tentang suatu keadaan secara objektif. Pengambilan data dilakukan dengan teknik total sampling dan didapatkan 32 sampel. Pasien yang terdiagnosis Osteoarthritis genu seluruhnya sebanyak 32(100,0%), mayoritas berusia 45-59 tahun 18 (56,3%), sebagian besar berjenis kelamin perempuan 27 (84,4%), dengan skor womac index terbanyak didapatkan berat sebanyak 16 (50,0%) dan range of motion aktif mayoritas terbatas pada kaki kanan dengan fleksi 29 (90,6%) dan ekstensi 19 (59,4%). Pasien Osteoarthritis genu seluruhnya sebanyak 32 pasien, mayoritas berusia 45-59 tahun, sebagian besar berjenis kelamin perempuan dengan hasil womac index didapatkan berat dan hasil range of motion aktif sebagian besar terbatas. Kata Kunci: Osteoarthritis, Womac Index, Range of Motion Aktif.